Susu Sapi sebagai Obat bagi Kesehatan Tubuh: Studi Takhrij dan Syarah Hadis - Hilma Noor Salwa Zakiyyah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss cow's milk as a medicine for body health. This study uses a qualitative type of method that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of this study can be concluded that the quality status of the hadith about cow's milk as a medicine for body health is assessed by hasan li ghairihi based on the takhrij hadith. And the hadith syarah shows that cow's milk is a medicine for the health of the body which in cow's milk contains many nutrients so that it is beneficial for the health of the body. The conclusion of this study is that the hadith about cow's milk as a medicine for body health can be referred to as an Islamic practice because it has hasan li ghairihi status.